2020
DOI: 10.1021/acs.langmuir.0c02561
|View full text |Cite
|
Sign up to set email alerts
|

Critical Detection of Agglomeration of Magnetic Nanoparticles by Magnetic Orientational Linear Dichroism

Abstract: Magnetic orientational linear dichroism (MOLD) spectroscopy was found to be useful for detecting the initiation of the agglomeration process of COOH-modified iron-oxide magnetic nanoparticles (MNPs) in water, which was produced by the addition of a small amount of a cationic surfactant or a metal ion. The critical association of MNPs leading to agglomeration was detected from the increase of the maximum MOLD value as well as from the shift of the maximum wavelength of the MOLD spectrum. The magnetic field depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…This may mean that the dispersion sample includes MNPs with different hydrodynamic diameters of monomers and oligomers; in the weaker magnetic field of 9 mT on the round cell, the oligomers of MNPs are preferentially oriented than the monomers, but in the stronger magnetic field of 27.5 mT on the 1 mm cell, almost all monomers and oligomers may be oriented because the magnetic moment is proportional to the number of MNPs. 28 Figure 6 shows the agreement between the observed CD spectra and the simulated CD spectra by the Mueller matrix method employing the observed LD and LB spectra for the two MNP concentrations. These results demonstrated that an optically chiral liquid can be produced by applying a helical weak magnetic field of 9 mT to a diluted MNP aqueous dispersion, and the optical chirality can be easily and reversibly switched by the change of the angle between the magnet fields.…”
Section: ■ Results and Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This may mean that the dispersion sample includes MNPs with different hydrodynamic diameters of monomers and oligomers; in the weaker magnetic field of 9 mT on the round cell, the oligomers of MNPs are preferentially oriented than the monomers, but in the stronger magnetic field of 27.5 mT on the 1 mm cell, almost all monomers and oligomers may be oriented because the magnetic moment is proportional to the number of MNPs. 28 Figure 6 shows the agreement between the observed CD spectra and the simulated CD spectra by the Mueller matrix method employing the observed LD and LB spectra for the two MNP concentrations. These results demonstrated that an optically chiral liquid can be produced by applying a helical weak magnetic field of 9 mT to a diluted MNP aqueous dispersion, and the optical chirality can be easily and reversibly switched by the change of the angle between the magnet fields.…”
Section: ■ Results and Discussionmentioning
confidence: 56%
“…Only one remarkable difference in the one-cell measurement was that the CD spectra had an isosbestic point at around 330 nm, which corresponded to the wavelength noted in LB spectra (Figure B). This may mean that the dispersion sample includes MNPs with different hydrodynamic diameters of monomers and oligomers; in the weaker magnetic field of 9 mT on the round cell, the oligomers of MNPs are preferentially oriented than the monomers, but in the stronger magnetic field of 27.5 mT on the 1 mm cell, almost all monomers and oligomers may be oriented because the magnetic moment is proportional to the number of MNPs Figure shows the agreement between the observed CD spectra and the simulated CD spectra by the Mueller matrix method employing the observed LD and LB spectra for the two MNP concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic torque was utilized for the orientation of diamagnetic microcrystals by a static magnetic field and the alignment of microcrystals by a modulated magnetic field, which served for X-ray diffraction analysis. 187 The magnetic orientation of MNPs was studied by linear dichroism spectroscopy 205 and Sagnac interferometry. 294 Here, again, the aggregation state of MNPs will severely affect the interpretation of the observation.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Watarai and Sakurai 205 observed that the magnetic orientational linear dichroism (MOLD) is very sensitive to the formation of small aggregates such as dimers and other oligomers of MNPs in solution. They measured the change in the MOLD spectra and shift in the maximum wavelength of COOH-modified MNP suspension by adding cationic surfactants or metal ions under a static magnetic field.…”
Section: Application Of Magnetic Torquementioning
confidence: 99%